INCORPORATING DIFFERENT SOURCE RUPTURE CHARACTERISTICS INTO SIMULATIONS OF STRONG GROUND MOTION FROM THE 1867, M7.0 EARTHQUAKE ON THE ISLAND OF LESVOS (NE AEGEAN SEA, GREECE) - Roumelioti, Z.; Kiratzi, A. (Bulletin of the Geological Society of Greece, 2010)
We apply the stochastic method for finite-faults (Beresnev and Atkinson, 1997, 1998) to simulate strong ground motion acceleration from the 1867 earthquake that devastated the Island of Lesvos in NE Aegean Sea. Recent geological data are taken into account to construct realistic models of the earthquake source, while a first-order approximation of the site effect variation throughout the entire island of Lesvos is achieved following an empirical approach suggested by Wald and Allen (2007). We test several source models including different segments of the Agia Paraskevi fault, which is most probably the seismogenic fault of the 1867 earthquake. Stronger ground motion is predicted in the central part of the island, i.e. around the assumed seismogenic structure. A significant site effect is evident along the eastern coast of Lesvos, where the capital of Mytilene lies, strongly hit by the 1867 earthquake, and around the gulfs of Kalloni and Geras in the south and southeast parts of the island. Synthetic peak ground acceleration values are converted to macroseismic intensities through an empirical relation and discussed in comparison with available reports on the macroseismic effects of the 1867 earthquake.